1992
DOI: 10.1136/bjo.76.5.280
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal intraocular pressure variations: an analysis of 690 diurnal curves.

Abstract: Out of a total of 2272 diurnal curves (DC) of intraocular pressure (IOP) obtained from 1178 patients 690 first curves of the right eye of all patients were analysed. For each DC there were 4-6 IOP readings taken between 8 am and 6.30 pm of the same day. The patients' diagnosis, age, sex, type of IOP lowering medication, diabetes, and the calendar month of the year were recorded. In 40% of cases the highest IOP was found at the earliest morning measurement with some 65% of peaks occurring before noon. The lowes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
178
3
10

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(208 citation statements)
references
References 6 publications
(2 reference statements)
15
178
3
10
Order By: Relevance
“…These results compare well with earlier studies on treated POAG. [8][9][10] However, these studies 8,9 except the one by Jonas et al 10 have reported IOP fluctuation during office hours in patients with POAG whose visual fields deteriorated despite acceptable office IOP levels or cases when a suspicious optic disc is discovered with normal office IOP. These patient groups may not truly represent treated POAG glaucoma as a whole.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These results compare well with earlier studies on treated POAG. [8][9][10] However, these studies 8,9 except the one by Jonas et al 10 have reported IOP fluctuation during office hours in patients with POAG whose visual fields deteriorated despite acceptable office IOP levels or cases when a suspicious optic disc is discovered with normal office IOP. These patient groups may not truly represent treated POAG glaucoma as a whole.…”
Section: Discussionmentioning
confidence: 88%
“…The treated POAG patients in previous studies on IOP fluctuation either do not truly represent treated POAG glaucoma as a whole or have issues in data collection. [8][9][10] Baskaran et al 6 enrolled study subjects after LPI but before commencement of any medical or surgical treatment. Current consensus recommends LPI in selected PACS eyes.…”
Section: Introductionmentioning
confidence: 99%
“…We did not control for diurnal variation in IOP, which has been reported to result in a mean range of 5.8 mmHg in patients with open-angle glaucoma. 24 Although our three IOP measurements taken at each baseline visit were from a 2 to 3 hour period of time, the time of day of these visits may have contributed to variation between visits.. A number of factors were associated with the mean IOP obtained in these newly diagnosed glaucoma patients prior to the onset of treatment. Older age was associated with lower IOP in our patients, which differs from that found in many population studies.…”
Section: Discussionmentioning
confidence: 99%
“…O propósito para a realização da CTD é detectar picos pressóricos não observados na rotina e que poderiam explicar a progressão do dano glaucomatoso (9)(10) . Cerca de 1/3 dos pacientes com Po aparentemente satisfatória em medidas de rotina apresentam picos ao longo das 24 horas (11) .…”
Section: Discussionunclassified